Vitamin D Levels and Cardiometabolic Markers in Indigenous Argentinean Children Living at Different Altitudes - Valeria Hirschler MD; Claudia Molinari MS; Gustavo Maccallini MS; Patricia Intersimone MS; Claudio Daniel Gonzalez MD (SAGE Publishing, 2019)
The objective of this study was to assess the association between vitamin D and cardiometabolic markers in 2 indigenous communities from similar ethnic backgrounds, but living at different altitudes. A cross-sectional study compared 152 (72 females) indigenous schoolchildren from San Antonio de los Cobres (SAC), 3750 m above sea level, with 175 (86 females) from Chicoana (CH), 1400 m above sea level, mean age 9 years. Anthropometry, blood pressure, lipids, glucose, insulin, and vitamin D were assessed in spring season. The prevalence of children's overweight/obesity was significantly lower in SAC, 9.2% (13), than in CH, 41.5% (71). There was a significantly higher prevalence of vitamin D deficiency (<20 ng/mL) in SAC (n = 103, 67.7%) than in CH (n = 62, 36.3%). SAC showed an inverse correlation between vitamin D and insulinemia ( r = −0.17, P < .05), whereas CH showed an inverse correlation between vitamin D and systolic blood pressure ( r = −0.19, P < .05), z -BMI (body mass index; r = −0.25, P < .01), triglycerides ( r = −0.15, P < .05), glucose ( r = −0.35, P < .05), and insulinemia ( r = −0.24, P < .01). Multiple linear regression analysis showed that vitamin D (β = −.47; R 2 = .21) was significantly associated with SAC location, adjusted for confounding variables. Vitamin D levels were significantly and directly associated with altitude and inversely with metabolic markers, suggesting that populations living at high altitudes are at higher risk for future cardiovascular diseases.